Il Vangelo secondo Tommaso e il platonismo: Considerazioni in margine a un recente volume - Annese, Andrea (Annali di storia dell'esegesi, 2020)
This article aims to scrutinize the hypothesis, proposed by some researchers, of Platonic or Platonizing influences in the Gospel of Thomas. The observations developed here are primarily stimulated by Ivan Miroshnikov’s recent volume, The Gospel of Thomas and Plato. A Study of the Impact of Platonism on the “Fifth Gospel” (Leiden, Brill 2018). After summarizing Miroshnikov’s theses, this article presents a series of observations in dialogue with them and other studies. The issue of the extent and character of possible Platonic influences on the Fifth Gospel will be examined, as well as the diffusion and reception of philosophical doctrines in a given cultural context (from the viewpoint of historical-religious trajectories), in particular in early Syriac Christian contexts.